Long-term clinical outcome of atrial fibrillation ablation in patients with history of mitral valve surgery - Almorad, Alexandre; O'Neill, Louisa; Wielandts, Jean-Yves; Gillis, Kris; De Becker, Benjamin; Nakatani, Yosuke; De Asmundis, Carlo; Iacopino, Saverio; Pambrun, Thomas; Marc, La Meir; Jaïs, Pierre; Haïssaguerre, Michel; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims Atrial fibrillation (AF) occurs frequently after mitral valve (MV) surgery. This study aims to evaluate the efficacy and long-term clinical outcomes after the first AF ablation in patients with prior MV surgery. Methods Sixty consecutive patients with a history of MV surgery without MAZE referred to three European centers for a first AF ablation between 2007 and 2017 (group 1) were retrospectively enrolled. They were matched (propensity score match) with 60 patients referred for AF ablation without prior MV surgery (group 2). Results After the index ablation, 19 patients (31.7%) from group 1 and 24 (40%) from group 2 had no recurrence of atrial arrhythmias (ATa) (p = 0.3). After 62 (48–84) months of follow-up and 2 (2–2) procedures, 90.0% of group 1 and 95.0% of group 2 patients were in sinus rhythm (p = 0.49). In group 1, 19 (31.7%) patients had mitral stenosis, and 41 (68.3%) had mitral regurgitation. Twenty-seven (45.0%) patients underwent mechanical valve replacement and 33 (55.0%) MV annuloplasty. At the final follow-up, 28 (46.7%) and 33 (55.0%) patients were off antiarrhythmic drugs (p = 0.46). ATa recurrence was seen more commonly in patients with prior MV surgery (54 vs. 22%, respectively, p < 0.05). No major complication occurred. Conclusion Long-term freedom of atrial arrhythmias after atrial fibrillation catheter ablation is achievable and safe in patients with a history of mitral valve surgery. In AF patients without a history of mitral valve surgery, repeated procedures are needed to maintain sinus rhythm.